Anthropomorphic tendencies in autism: A conceptual replication and extension of White and Remington (2019) and preliminary development of a novel anthropomorphism measure. (May 2022) - Clutterbuck, Rachel A; Shah, Punit; Leung, Hok Sze; Callan, Mitchell J; Gjersoe, Natalia; Livingston, Lucy A
White and Remington (2019) found that autistic people may have increased anthropomorphic tendencies to ascribe human-like attributes to non-human agents. However, it was unclear from their study whether this relationship holds after accounting for socio-demographic variables known to be associated with anthropomorphism. The psychometric properties of the anthropomorphism questionnaire they used has also not been investigated, raising concerns about whether it measures the same construct in people with differing levels of autistic traits. Addressing these issues, we re-examined the relationship between autism and anthropomorphism in a large sample of adults ( N = 492). Conceptually replicating White and Remington, we found that autistic traits were significantly associated with greater anthropomorphic tendencies, even after accounting for age and sex (Study 1). Equally, psychometric concerns with the anthropomorphism questionnaire were revealed, leading us to refine this measure and re-analyse the data. A less clear-cut but significant association between autistic traits and anthropomorphism was found (Study 2). Our refined anthropomorphism measure also had improved psychometric properties, particularly showing that it is suitable for future autism research. Our findings are discussed in relation to individual differences in social-cognitive processing and we outline future directions for investigating mechanisms linking anthropomorphism and social cognition in autism. Lay abstract: Anthropomorphism is the tendency to attribute human-like qualities (e.g. thoughts and feelings) to non-human entities (e.g. objects and weather systems). Research by White and Remington (2019) suggested that anthropomorphism is more common in autistic compared to neurotypical adults, which is interesting given that autistic individuals sometimes misunderstand the thoughts and feelings of other people. In this article, we re-examined the link between autism and anthropomorphism in a large sample of adults with varying degrees of autistic traits, with several important methodological advances on previous research. Across two studies, we found that individuals with more autistic traits reported greater anthropomorphic tendencies. As part of these analyses, we had to develop a new, refined measure of anthropomorphism, which showed better reliability and validity than the original measure. This measure will be useful in future autism-related research. Overall, advancing White and Remington's study, these findings help us to better understand individual differences in socially relevant processes, including those that may be enhanced in autism (e.g. anthropomorphism).